2020
DOI: 10.1155/2020/3852421
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Lattice Strain, Morphology, and Electrical Properties of SnO2 Nanoparticles Induced by Low Calcination Temperature

Abstract: The electrical properties of tin dioxide (SnO2) nanoparticles induced by low calcination temperature were systematically investigated for gas sensing applications. The precipitation method was used to prepare SnO2 powders, while the sol-gel method was adopted to prepare SnO2 thin films at different calcination temperatures. The characterization was done by X-ray diffraction, scanning electron microscopy (SEM), and atomic force microscopy (AFM). The samples were perfectly matched with the rutile tetragonal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…This increase in crystallite size is due to the growth of the crystals as a result of high calcination temperature. High calcination temperature provides sufficient kinetic energy for the migration of grain boundaries and small crystals fuse to form large sized particles [45,51] . These findings were also confirmed by FE‐SEM images which clearly show the formation of inter‐particle necks due to the coalescence of small crystals.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This increase in crystallite size is due to the growth of the crystals as a result of high calcination temperature. High calcination temperature provides sufficient kinetic energy for the migration of grain boundaries and small crystals fuse to form large sized particles [45,51] . These findings were also confirmed by FE‐SEM images which clearly show the formation of inter‐particle necks due to the coalescence of small crystals.…”
Section: Resultssupporting
confidence: 53%
“…As the calcination temperature increases, the intensity of the peaks shows an increase, confirming increase in the crystallinity. The appearance of sharp and high intensity peaks indicates that the synthesized nanocomposite has high crystallinity [45–47] . Thus higher calcination temperature provides sufficient energy to form a highly crystalline form.…”
Section: Resultsmentioning
confidence: 99%
“…This finding matches with the XRD results and the fact that the SnO 2 crystallizes into polymorphs of cassiterite, the rutilelike type phase (of space group P4 2 /mnm), while the most stable form of SnO is the so-called litharge tetragonal crystal structure (P4/nmm). 32 In addition, it was previously found that, in general, tin oxides deposited at elevated partial pressures of oxygen consist of the rutile-like SnO 2 form, while low pressures of oxygen result in SnO. 33 Such morphological transformation may be attributed to oxygen vacancies due to partial deficiency of oxygen atoms, with reduction of some Sn 4+ ions to Sn 2+ as a possible charge compensation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that there is a crystal growth after hot-press sintering. Further, the Scherrer-Gottingen formula is used to estimate the micro lattice strain of BTS (∼0.038) and Bi 6 O 7 (∼0.054) phases, presented in the hot-pressed pellet by choosing peaks at 27.82 • , 29.26 • , respectively [35]. The XRD patterns in both ⊥ to PA and || to PA look the same.…”
Section: Methodsmentioning
confidence: 99%